2018
DOI: 10.1002/2017jg004356
|View full text |Cite
|
Sign up to set email alerts
|

Source Partitioning of Methane Emissions and its Seasonality in the U.S. Midwest

Abstract: The methane (CH4) budget and its source partitioning are poorly constrained in the Midwestern United States. We used tall tower (185 m) aerodynamic flux measurements and atmospheric scale factor Bayesian inversions to constrain the monthly budget and to partition the total budget into natural (e.g., wetlands) and anthropogenic (e.g., livestock, waste, and natural gas) sources for the period June 2016 to September 2017. Aerodynamic flux observations indicated that the landscape was a CH4 source with a mean annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The monthly average concentration footprints are also shown in Figure S4. Previous studies have defined the most sensitive zone as the source areas with a footprint smaller than 10 −4 ppm m 2 s/μmol (Chen et al, , ; Kim et al, ). C. Hu, Liu, et al () and C. Hu, Griffis, et al () quantified a threshold of 10 −3 ppm m 2 s/μmol as the intense source area defined where 80% of the CO 2 enhancement was realized.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The monthly average concentration footprints are also shown in Figure S4. Previous studies have defined the most sensitive zone as the source areas with a footprint smaller than 10 −4 ppm m 2 s/μmol (Chen et al, , ; Kim et al, ). C. Hu, Liu, et al () and C. Hu, Griffis, et al () quantified a threshold of 10 −3 ppm m 2 s/μmol as the intense source area defined where 80% of the CO 2 enhancement was realized.…”
Section: Resultsmentioning
confidence: 99%
“…The Stochastic Time‐Inverted Lagrangian Transport (STILT) model is a receptor‐oriented model and has been widely applied in the transport simulation of many trace gases including CH 4 (Chen et al, ; Verhulst et al, ), CO 2 (Graven et al, ; C. Hu, Griffis, et al, ; C. Hu, Liu, et al, ), N 2 O (Chen et al, ; Griffis et al, ), and CO (Kim et al, ). The STILT model can accurately simulate the source footprint (influence‐weighting functions) for a given receptor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work used a threshold of 1e −4 ppm m 2 · s/μmol, to define the most sensitive zone (shown as red) for the investigation of CO, N 2 O, and CH 4 (Kim et al, ; Chen et al, , ). At our same site, Chen et al concluded that about 30% of the CH 4 enhancement was contributed by an area defined by a footprint function threshold of 1e −4 ppm m 2 · s/μmol, and most of the U.S. Corn Belt is contained within the most sensitive and intense footprint zone and, thereby, included the dominant influence of agricultural crops (mainly corn and soybean). For the case of CO 2 , the most sensitive zone is quite different because of the strongly heterogeneous distribution of anthropogenic CO 2 emissions.…”
Section: Resultsmentioning
confidence: 99%